Dodecapeptide Cathelicidins of Cetartiodactyla: Structure, Mechanism of Antimicrobial Action, and Synergistic Interaction With Other Cathelicidins - Bolosov, Ilia A.; Panteleev, Pavel V.; Sychev, Sergei V.; Sukhanov, Stanislav V.; Mironov, Pavel A.; Myshkin, Mikhail Yu.; Shenkarev, Zakhar O.; Ovchinnikova, Tatiana V. (Frontiers in Microbiology, 2021)
In this study, dodecapeptide cathelicidins were shown to be widespread antimicrobial peptides among the Cetruminantia clade. In particular, we investigated the dodecapeptide from the domestic goat Capra hircus, designated as ChDode and its unique ortholog from the sperm whale Physeter catodon (PcDode). ChDode contains two cysteine residues, while PcDode consists of two dodecapeptide building blocks and contains four cysteine residues. The recombinant analogues of the peptides were obtained by heterologous expression in Escherichia coli cells. The structures of the peptides were studied by CD, FTIR, and NMR spectroscopy. It was demonstrated that PcDode adopts a β-hairpin structure in water and resembles β-hairpin antimicrobial peptides, while ChDode forms a β-structural antiparallel covalent dimer, stabilized by two intermonomer disulfide bonds. Both peptides reveal a significant right-handed twist about 200 degrees per 8 residues. In DPC micelles ChDode forms flat β-structural tetramers by antiparallel noncovalent association of the dimers. The tetramers incorporate into the micelles in transmembrane orientation. Incorporation into the micelles and dimerization significantly diminished the amplitude of backbone motions of ChDode at the picosecond-nanosecond timescale. When interacting with negatively charged membranes containing phosphatidylethanolamine (PE) and phosphatidylglycerol (PG), the ChDode peptide adopted similar oligomeric structure and was capable to form ion-conducting pores without membrane lysis. Despite modest antibacterial activity of ChDode, a considerable synergistic effect of this peptide in combination with another goat cathelicidin - the α-helical peptide ChMAP-28 was observed. This effect is based on an increase in permeability of bacterial membranes. In turn, this mechanism can lead to an increase in the efficiency of the combined action of the synergistic pair ChMAP-28 with the Pro-rich peptide mini-ChBac7.5Nα targeting the bacterial ribosome.